2017
DOI: 10.1080/23328940.2017.1356427
|View full text |Cite
|
Sign up to set email alerts
|

Sports and environmental temperature: From warming-up to heating-up

Abstract: Most professional and recreational athletes perform pre-conditioning exercises, often collectively termed a 'warm-up' to prepare for a competitive task. The main objective of warming-up is to induce both temperature and non-temperature related responses to optimize performance. These responses include increasing muscle temperature, initiating metabolic and circulatory adjustments, and preparing psychologically for the upcoming task. However, warming-up in hot and/or humid ambient conditions increases thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 306 publications
1
124
0
2
Order By: Relevance
“…To proper evaluate the human body thermal behavior it is necessary to take into account these exchanges, and according to ASHRAE [14] and other authors 7,15 , the energy balance can be described according to Equation (1).…”
Section: The First Law Of Thermodynamics Applied To the Human Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…To proper evaluate the human body thermal behavior it is necessary to take into account these exchanges, and according to ASHRAE [14] and other authors 7,15 , the energy balance can be described according to Equation (1).…”
Section: The First Law Of Thermodynamics Applied To the Human Bodymentioning
confidence: 99%
“…The body temperature has always been considered as an indicator of health. Lavoisier (1743-1794) showed that humans generate heat by a combustion process resulting in the production of carbon dioxide and consumption of oxygen 1 . VO 2 max, running economy, fractional utilization of VO 2 max and lactate threshold are used for health status, evaluation of training intensity and improving the performance of endurance in athletes 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fat oxidation is observed to be maximal at lower to moderate exercise intensities ranging from 33%-65% VO 2 max. 11,26,27 However, it has been reported that cold exposure during exercise can increase lipid utilization when cold exposure is sufficient to cause a decrease in Tre during exercise. A previous study observed lower RER during 90 minutes of exercise at 65% VO 2 max in 5°C compared to 20°C, with lowered Tre observed during the cold condition.…”
Section: Submaximal Exercisementioning
confidence: 99%
“…Physical exercise in hot conditions with or without dehydration may also induce hyperthermia. This causes cardiovascular strain which limits exercise performance and may even lead to serious heat associated health conditions ( Crandall and Gonzalez-Alonso, 2010 ; Yankelson et al, 2014 ; Brocherie et al, 2015 ; Racinais et al, 2017 ), which include heat rash, syncope, heat cramps, heat exhaustion, and heat stroke ( Howe and Boden, 2007 ; Brocherie et al, 2015 ; Racinais et al, 2017 ). The responses of subjects exposed to a hot environment will depend on type, duration and intensity of exercise, as well as additional factors (i.e., related to body composition, clothing or other weather independent variables) ( Brocherie et al, 2014 ).…”
Section: Humans Exposed To Extreme Environmental Temperaturesmentioning
confidence: 99%
“…With respect to exercise performance, a reduction in cardiac output, stroke volume, arterial pressure and blood flow to the brain, skin and exercising muscles have been observed prior to exhaustion ( Crandall and Gonzalez-Alonso, 2010 ; Akerman et al, 2016 ). Hyperthermia may also impair central as well as peripheral neuromuscular function ( Racinais et al, 2017 ).…”
Section: Humans Exposed To Extreme Environmental Temperaturesmentioning
confidence: 99%